What We Talk about When We Talk about Unconscious Processing – A Plea for Best Practices - Rothkirch, Marcus; Hesselmann, Guido (Frontiers in Psychology, 2017)
In this perspective article, we first outline the large diversity of methods, measures, statistical analyses, and concepts in the field of the experimental study of unconscious processing. We then suggest that this diversity implies that comparisons between different studies on unconscious processing are fairly limited, especially when stimulus awareness has been assessed in different ways. Furthermore, we argue that flexible choices of methods and measures will inevitably lead to an overestimation of unconscious processes. In the concluding paragraph, we briefly present solutions and strategies for future research. We make a plea for the introduction of “best practices”, similar to previous attempts to constitute practicing standards for functional magnetic resonance imaging (fMRI) and electroencephalography (EEG).